Program Desa Membangun di Desa Tamaila - Yayu Indriati Arifin; Irvin Novita Arifin (Univeristas Negeri Gorontalo, 2022)
Tamaila Village is one of the villages located in Tolangohula District, Gorontalo Regency, Gorontalo Province, astronomically located at the coordinates of N 0044'27.9